2019
DOI: 10.12693/aphyspola.135.229
|View full text |Cite
|
Sign up to set email alerts
|

Phase Structure and Heating Efficiency of As-Synthesised Iron-Oxide Nanoparticles and after Long Time Storage in Glycerol

Abstract: In the present work the structural characteristics and heating efficiencies of iron-oxide nanoparticles were studied. The investigated samples were produced by co-precipitation of Fe-O nanoparticles from mixture of Fe 2+ and Fe 3+ salts in the alkaline environment. Furthermore, the influence of processing route and storage environment on the phase structure and heating efficiency was studies for glycol dispersed nanoparticles. The heating efficiency experiments were performed on 5 wt% glycerol dispersions of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…However, due to the low saturation magnetization of these samples, their dispersions subjected to high-frequency external magnetic fields have shown a rather weak T(t) response. It was found that SLP and ILP values were relatively low compared to those measured for magnetite NPs co-precipitated using standard procedures [9,38,39,53].…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…However, due to the low saturation magnetization of these samples, their dispersions subjected to high-frequency external magnetic fields have shown a rather weak T(t) response. It was found that SLP and ILP values were relatively low compared to those measured for magnetite NPs co-precipitated using standard procedures [9,38,39,53].…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, the effect of a slightly higher d b than d t for dispersions used for measurements should not be neglected. Much lower SLP values for studied AeroNPs compared to SLP measured for dispersion of bare co-precipitated Fe 3 O 4 nanoparticles [38,39] and these coated with TEA-oleate [9] might be related to the smaller sizes of the 2AeroNPs-top and 2AeroNPs-bottom and their smaller agglomerates formed before coating them with TEA-oleate. The possible factor that might influence the differences in obtained SLP is the impact of TEA-oleate coating on the magnetic properties of the nanoparticles.…”
Section: Magnetic Heating Efficiency Of Aeronps Dispersionmentioning
confidence: 80%
See 2 more Smart Citations